Flow simulation in coronary artery models: An investigation of the effect of variable angulations at left coronary artery - Chachaina, T.; Sun, Zhonghua; Tungjitkusolmun, S.; Sangworasil, M. (Curtin University, 2010)
This study was designed to investigate the hemodynamics in the left coronary artery with the aim of identifying the relationship between angulations of left coronary bifurcation and development of atherosclerosis. Six 3D left coronary models were simulated for computational fluid dynamic analysis. The left coronary model was composed of left main stem, left anterior descending and left circumflex branches. The angulations at the left bifurcation weresimulated with angles ranging from 90°, 75°, 60°, 45°, 30° to 15°. The computational fluid dynamic was used for analysis of flow velocity, wall pressure and wall shear stress. Our results showed that apparent low shear stress and high wall pressure was noticed at the left coronary bifurcation regions with wide angled models. Flow pattern was also changed with angled becoming wide in the simulated models. Our analysis shows direction relationship between coronary angulation and development of atherosclerosis. Future studies are required to perform computational fluid dynamic analysis in coronary models from patients' data with different degree of coronary stenosis.